Pattern of Eye Disease in Nenwe Rural Eye Clinic, Nigeria: A Seven Year Review - Ozioko, Nnenna Maureen; Okoloagu, Nkiru Mary; Onah, Emmanuel Sunday; Catherine, Dr. (International Journal of Clinical and Experimental Ophthalmology, 2024)
Background: The establishment of eye clinics in the form of rural outreach centers as a means of educating and providing eye care to rural residents was made necessary by the lack of eye care services in rural areas within Nigeria and the need to increase the cataract surgical rate among ophthalmologists in training. Understanding patterns of eye diseases in rural areas and eye health-seeking behaviors is crucial to achieving the goals of Vision 2020 especially for aspiring ophthalmologists. Aim and objectives: To examine the types of eye conditions observed at Nenwe, a rural outreach post of a tertiary hospital, and to evaluate their distribution. Methodology: A retrospective analysis of all patients who were seen at the community eye clinic during seven years was carried out. Records of patients at the Nenwe outreach eye clinic dating from November 2016 to August 2023 were examined, yielding information on patients examined during the period of study. Results: Glaucoma was the most common eye condition to be diagnosed. Cataracts were the second most common eye condition accounting for 20.8%. Other common eye illnesses were refractive error (9%), pterygium (7%), and allergic eye disease (6%) with 129, 101, and 95 cases, respectively. Retinal detachment (51 cases), prebyopia (47 cases), corneal lesion (58 cases), and dry eye condition (47 cases) were less common. Conclusion: The results show the burden of eye disorders in the Nenwe rural community and the importance of community-based eye care services.